DESAIN SISTEM PROTEKSI OVERCURRENT DAN GROUND FAULT RELAY UNTUK JARINGAN TEGANGAN MENENGAH MENGGUNAKAN ETAP 19.0.1 - M.Wahyu Prawindu; Muhammad Ilham Hasibbuan; Hutur P Siahaan; Arwadi Sinuraya; Desman Jonto Sinaga (JOURNAL SAINS STUDENT RESEARCH, 2025)
Medium-voltage (20 kV) power distribution systems are highly susceptible to short-circuit faults and single line-to-ground faults. To ensure system reliability and supply continuity, a protection scheme that is selective, fast, and adaptive to real network conditions is essential. This study aims to design a protection system based on Overcurrent Relays (OCR) and Ground Fault Relays (GFR) using the ETAP 19.0.1 software. The methodology includes single-line system modeling, fault simulations, and analysis of Time-Current Characteristic (TCC) curves and relay selectivity. Simulation results indicate that all relays operate within a selective time range (0.12 s – 0.65 s) without curve overlaps. The minimum selectivity factor (Ks) achieved is 2.1, exceeding the standard threshold of 1.8 for isolated-neutral systems. The proposed design provides reliable protection against high-resistance faults and is suitable for practical implementation in Indonesia’s distribution networks.